The progress of the Reformation in South Northamptonshire, c. 1510 – c. 1750 - Garfield, Ann (2016)
The thesis follows the stages of the Reformation from the late-medieval Church to the Elizabethan Church and later Separatist groups in eighteen parishes of the upper River Tove valley. A number of ideas and assumptions about the Reformation have been tested for the area. An important finding is that even in this small area the timing and pace of the Reformation varied between individual parishes and occurred in different ways. There is shown to have been a diversity and variety of piety between and within communities across the period of the study. It is shown that changes had begun before the Dissolution, making Henry VIII’s reforms easier to accept; that there was no Marian revival of Catholicism in the area; and that the main element in the timing of reform was the different influences at work in the parishes. After an introductory chapter, evidence is presented in five more chapters that are entitled: the Study Area; the Late-medieval Church; Wills and Religious Beliefs; Influences in the Parishes; and the Growth of Dissent. These are followed by a Conclusion, outlining the main findings of the thesis, the advantages of the methodology used, and how the thesis is a new type of study of the Reformation.